Heterogeneous contributions of change in population distribution of body mass index to change in obesity and underweight - NCD Risk Factor Collaboration (NCD-RisC) (eLife, 2022)
This article was published in the Epidemiology and Global Health by eLife [distributed under the terms of the Creative Commons Attribution License] and the definite version is available at: https://doi.org/10.7554/eLife.60060 The Journal's website is at: https://elifesciences.org/articles/60060